2008
DOI: 10.1074/jbc.m707985200
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Shear Stress Up-regulates Peroxiredoxins (PRX) in Endothelial Cells

Abstract: Shear stress plays a significant role in endothelial cell biology and atherosclerosis development. Previous work by our group has shown that fluid flow stimulates important functional changes in cells through protein expression regulation. Peroxiredoxins (PRX) are a family of antioxidant enzymes but have yet to be investigated in response to shear stress. Studies have shown that oscillatory shear stress (OS) increases reactive oxygen species (ROS) levels in endothelial cells, whereas laminar shear stress (LS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 44 publications
2
55
1
1
Order By: Relevance
“…This may be due to incomplete depletion of intracellular GSH or the presence of other defense mechanisms such as superoxide dismutase and peroxiredoxins (16,25). Although our data indicated that GSH plays a critical role in antioxidant defense by LSS, association of other antioxidants such as L-ascorbic acid and ␣-tocopherol cannot be excluded.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This may be due to incomplete depletion of intracellular GSH or the presence of other defense mechanisms such as superoxide dismutase and peroxiredoxins (16,25). Although our data indicated that GSH plays a critical role in antioxidant defense by LSS, association of other antioxidants such as L-ascorbic acid and ␣-tocopherol cannot be excluded.…”
Section: Discussionmentioning
confidence: 61%
“…The regions of arteries experiencing laminar shear stress (LSS) due to orderly blood flow are usually protected from atherosclerotic lesion formation, and thus LSS of relatively high level has been proposed to play anti-atherogenic roles. Differently from oscillatory shear stress, LSS usually does not stimulate inflammatory reactions but suppresses them probably by increasing nitric oxide (NO) production rather than reactive oxygen species (ROS) (8) or by induction of enzymes associated with antioxidant defense (25).…”
mentioning
confidence: 99%
“…These isoforms regulate intracellular levels of H2O2 (91). Prdx1 is induced in macrophages by oxLDL exposure (92) and in endothelial cells by laminar shear stress (93). Prdx1 deficiency results in the excessive release of P-selectin and von Willebrand factor, proinflammatory components of Weibel-Palade bodies (94).…”
Section: Peroxiredoxins In Cardiovascular Diseasesmentioning
confidence: 99%
“…A recent study showed that laminar shear stress, but not oscillatory shear stress, increased expression of antioxidant enzyme peroxiredoxins by ECs. 50 …”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%